PENAMBAHAN TEPUNG SUMBER β-KAROTEN ALAMI DALAM PAKAN TERHADAP PENINGKATAN KECERAHAN WARNA DAN PERTUMBUHAN IKAN KOI (Cyprinus carpio) - Purba, Mustika; Putriningtias, Andika; Komariyah, Siti (Universitas Teuku Umar, 2020)
Koi fish (Cyprinus carpio) is a high-economic ornamental fish which is still included in the relatives of carp. Koi fish have colorful body colors with various types and patterns. The color of ornamental fish is one of the attractions of koi fish lovers. One of the efforts to increase the brightness of koi fish is the addition of color material from natural sources. This study aims to analyze the effect of adding flour containing different natural beta-carotene to the brightness of the color and growth of koi fish. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments with 3 replications. The treatment of this research is control or without the addition of beta-carotene source flour (P1), addition of mangosteen rind flour flour (P2), addition of dragon fruit skin flour (P3), and addition of crab shell flour (P4). Observed research parameters include Color Enhancement, LPBH (Daily Weight Growth Rate), Absolute Weight Growth, Absolute Length Growth, EP (Feed Efficiency), Survival Rate and water quality. The results showed that the Color Enhancement ranged from: 9.97 - 12.85, LPBH: 1.71% - 2.23%, Absolute Weight: 4.07g - 6.17g, Absolute Length: 1.55cm - 2.68cm , EP: 51.35% - 61.42%, SR: 86.67% - 100%. The results of analysis of variance were carried out that the increase in color, absolute weight and absolute length had a significant effect on koi fish (Cyprinus carpio). The addition of crab shell flour (P4) is the best result for the improvement of the color of koi fish (Cyprinus carpio) compared to the addition of dragon fruit peel flour and mangosteen flour.